2020
DOI: 10.1186/s12889-020-09603-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of socio-demographic determinants in the geo-spatial distribution of newly diagnosed HIV infections in small areas of Catalonia (Spain)

Abstract: Background Spatial visualization of HIV surveillance data could improve the planning of programs to address the HIV epidemic. The objectives of the study were to describe the characteristics and the spatial distribution of newly diagnosed HIV infection in Catalonia and to identify factors associated with HIV infection rates. Methods Surveillance data from the national registry were presented in the form of descriptive and ring maps a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
3
0
2
Order By: Relevance
“…Sexual behaviour is, in this respect, probably the most important factor, for example, MSM are advised to test regularly 31. However, factors such as sexual behaviour, partner selection and sociocultural determinants that are (partly) affected by residential area were indirectly included in the analyses by accounting for area characteristics 9–13 32. Fourth, we only had GP testing data from one laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual behaviour is, in this respect, probably the most important factor, for example, MSM are advised to test regularly 31. However, factors such as sexual behaviour, partner selection and sociocultural determinants that are (partly) affected by residential area were indirectly included in the analyses by accounting for area characteristics 9–13 32. Fourth, we only had GP testing data from one laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…This is partly due to the selection of sexual partners nearby one’s own residential location 9–11. In addition, sociocultural determinants of a specific area may influence spatial clustering of STIs 12 13…”
Section: Introductionmentioning
confidence: 99%
“…Sabe-se que a urbanização e o desenvolvimento das grandes cidades influenciam na disseminação de infecções, principalmente pelo HIV (27) . Estudo realizado na Catalunha, Espanha, identificou que as maiores taxas de novos diagnósticos de HIV ocorreram em regiões localizadas em áreas urbanas, especialmente na cidade de Barcelona (28) . Outra pesquisa realizada nos Estados Unidos revelou diferenças estatisticamente significativas na distribuição de novos diagnósticos por características demográficas e ambiente urbano, com taxas de positividade para o HIV mais altas nas áreas urbanas (29) .…”
Section: Discussionunclassified
“…The urbanization and development in big cities are known to influence the spread of infections, especially HIV ( 27 ) . A study conducted in Catalonia, Spain, identified that the highest rates of new HIV diagnoses occurred in regions located in urban areas, especially in the city of Barcelona ( 28 ) . Another study conducted in the United States revealed statistically significant differences in the distribution of new diagnoses by demographic characteristics and urban environment, with higher HIV positivity rates in urban areas ( 29 ) .…”
Section: Discussionmentioning
confidence: 99%